Classroom Action Research in IPAS Learning: Enhancing Students' Cognitive Abilities through a Differentiated Approach in Elementary Schools - Lidiawati; Eddy Haryanto; Ahmad Habibi (Lembaran Ilmu Kependidikan, 2025)
Background - In the era of the Merdeka Curriculum, fostering cognitive development through inclusive and student-centered instruction is a key priority, especially in integrated science and social studies (IPAS) for elementary students. Purpose - This study aims to improve students’ cognitive abilities in the IPAS subject through the implementation of differentiated learning strategies in a fourth-grade elementary classroom. Method/approach - This research employed Classroom Action Research (CAR) following the Kemmis & McTaggart model, which consists of two iterative cycles involving planning, implementation, observation, and reflection. Data collection techniques included cognitive assessments, classroom observations, teacher interviews, and documentation. The data were analyzed using both qualitative and quantitative descriptive methods. Findings - The results indicated a significant improvement in students' cognitive performance: 29% of students achieved the competency standard in the pre-cycle, which increased to 50% in Cycle I, and further to 86% in Cycle II. In addition to improved academic outcomes, students showed higher motivation, active participation, and greater confidence in connecting IPAS concepts to real-life contexts. Conclusions - The implementation of differentiated learning proved effective in enhancing cognitive understanding and fostering a more interactive and inclusive classroom atmosphere. This approach supports the goals of the Merdeka Curriculum by addressing diverse learning needs. Novelty/Originality/Value - This study provides empirical evidence on the practical application of differentiated instruction in IPAS learning at the elementary level, demonstrating its value in promoting equity, engagement, and academic success in line with current curriculum reforms.